التحليل النحوي لاسم المعرفة في سورة الغاشية: Analisa Sintaksis Nomina Definit pada Surah Al-Ghasyiyah - Makhisoh, Iis (Jiluna Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
The aim of this research is to analyze and identify isim marifat, or definite nouns, in the Al-Qur'an, which focuses on al-Ghasyiyah. The results of syntactic analysis, which focuses on definite nouns, or Isim makrifat, found that not all verses in the letter contain these nouns. It is only found in 16 verses, including: in the first verse, there is one noun in the form Isim, which includes ال in the word الغاسية; in verse 6, there is one Isim Ma'rifat in the form of Isim Dhomir. This noun is also established in verses 9, 11, 12, and 13, in the form Isim dhomir ها. In verses 17, 18, 19, and 20, it is established in the form ال in the words-الابل ،السما ،الجبال ،الارض. Then, in verse 21, two Isim ma'rifat are established in the form of Isim maushul ما and Isim dhomir munfashil انت. In verse 22, there is one definite noun in the form of Isim dhomir muttashil. Namely, in verse 23, there is one Isim Ma'rifat in the form of Isim Maushul in the form of من. Also, this noun is established in verse 24 by four nouns in the form of one Isim dhomir and three Isim by ال. In verse 25, there are two Isim ma'rifat in the form of Isim dhomir muttashil mahal jer،هم نا, and in verse 26, there are two Isim ma'rifat in the form of Isim dhomir muttashil mahal jer نا ،هم. In terms of the function of the I'rob definite noun or Isim Ma'rifat in the alghosiyah letter, there are three types, namely one Rafa'/nominative noun, five Nashab/accusative nouns, and 16 nouns with the Jer/genetive function.